Zastosowanie analizy wideo w zdalnym nauczaniu fizyki - Ihor Chernetskyi; Iryna Slipukhina; Fabian Andruszkiewicz (Edukacja Ustawiczna Dorosłych)
Distance learning in the years 2020-2021 resulted in a much greater focus on the problem of shaping the ability to use digital tools by science teachers. In this context, interest in using video analysis tools in remote teaching science subjects such as physics, mathematics, chemistry, and others has increased significantly. The research problem undertaken in the work was defined as follows: is the analysis of video recordings an effective tool for remote teaching of physics at various levels of education? Tracker: Video Analysis and Modeling Tool provides physical data from moving and still image processing and mathematical modeling for descriptive and predictive lab exercises and educational experiments. The principles of creating educational films suitable for analysis in this digital environment have also been generalized. In the STEM laboratory of the National Center “Junior Academy of Sciences of Ukraine,” model video recordings of physical experiments were created, and the possibilities of their use in teaching were determined; a collection of video recordings with assigned tasks was created, and original methods of conducting educational physics experiments were developed. Video analysis is a unique technology that can not only enhance science and math lessons but also deepen students’ understanding of the scientific basis of observed phenomena and processes formalized in formulas, graphical and algebraic data. Teaching methods that use video analysis were used both in formal and informal education, in distance learning (caused, inter alia, by the COVID-19 pandemic), in the all-Ukrainian online tournament in natural sciences “Open Natural Shows,” in summer science schools for students, in teacher training, seminars, and educational conferences. It can be expected that video analysis in teaching physics will broaden the understanding of ways to acquire scientific knowledge and effectively shape the skills of using digital tools among all participants of the educational process.